Helvete 3 Bleeding Black Noise (Punctum Books, 2016)
Not to be confused with metal studies, music criticism, ethnography, or sociology, Helvete: A Journal of Black Metal Theory is a speculative and creative endeavor, one which seeks ways of thinking that count as Black Metal events - and indeed, to see how Black Metal might count as thinking. Theory of Black Metal, and Black Metal of theory. Mutual blackening. Therefore, we eschew any approach that treats theory and Metal discretely, preferring to take the left-hand path by insisting on "some kind of connaturality between the two, a shared capacity for nigredo." Black Metal Theory is noise. Lacking one clear manifesto or position, it fails to become an elite circle. It is amplified and transmitted electronically: through instruments, lo-fi recordings, internets, and print-on-demand publishers...yet rather than a clear direction of progress we glean only its subversive raw dissonance, disruptions, animalistic screams, resonating disturbances, high-pitched feedback, primitive growls, and its atmospheric statics, hisses, and drones. Black Metal Theory refuses to be hi-fi. It quenches its sonic thirsts from primordial-ditch stews that resemble the dark sludge of recently melted snowfall - pristine white flakes transmuted into a tumultuously sexy and delicious mixture of trash and dirt and ash and poison that swirls and splashes in ditches before seeping into the underground. Our ears drink this disharmonious black bile and our bodies suspend in its intoxicating formless complexities. The third issue of Helvete, "Bleeding Black Noise," features artwork and essays that focus on the sonic aspects of Black Metal, specifically its interactions with Noise - the interruptions, creations, and destructions of signals. "Bleeding Black Noise" is a revision of Steven Parrino's statement, "My relation between Rock and visual art: I will bleed for you." In this issue, Rock is replaced with Noise, and Bleeding is celebrated as a release of the Black Noise - raw energy and formless potential. The essays and art portfolios included here experiment with sonic and conceptual feedback, as well as the way that black noise works through feedback as a process, resonating as background hums or drones, and cascading in foregrounded screams.